2021
DOI: 10.3390/cells10092352
|View full text |Cite
|
Sign up to set email alerts
|

Elongational Stresses and Cells

Abstract: Fluid forces and their effects on cells have been researched for quite some time, especially in the realm of biology and medicine. Shear forces have been the primary emphasis, often attributed as being the main source of cell deformation/damage in devices like prosthetic heart valves and artificial organs. Less well understood and studied are extensional stresses which are often found in such devices, in bioreactors, and in normal blood circulation. Several microfluidic channels utilizing hyperbolic, abrupt, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 115 publications
(242 reference statements)
1
8
0
Order By: Relevance
“…For the highest sample flow rate tested in this study (i.e., 10 mL h −1 ), our numerical studies show that cells experience an average shear stress of 21.11 Pa for less than 5 ms (maximum of 186.15 Pa for less than 100 µs) in the narrow constriction. It has been reported that such values for shear along with the corresponding short exposure times maintain cell viability and function [76][77][78], as confirmed by our viability tests. Another important point to discuss is the use of ultralow-conductivity DEP buffer in this study.…”
Section: Discussionsupporting
confidence: 89%
“…For the highest sample flow rate tested in this study (i.e., 10 mL h −1 ), our numerical studies show that cells experience an average shear stress of 21.11 Pa for less than 5 ms (maximum of 186.15 Pa for less than 100 µs) in the narrow constriction. It has been reported that such values for shear along with the corresponding short exposure times maintain cell viability and function [76][77][78], as confirmed by our viability tests. Another important point to discuss is the use of ultralow-conductivity DEP buffer in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Extensional flow is prevalent in a number of contexts with regard to blood flow, including constrictions in the microcirculation [ 42 ], severe arterial stenosis due to cardiovascular disease [ 13 ], jetting through artificial heart valves [ 16 ], entrance and exit of ventricular assist devices [ 16 ], and under conditions of turbulent flow [ 15 , 43 ]. Extensional flow is most commonly seen when vessels transition in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, platelet responses to other hemodynamic forces over short timescales, prevalent in the vasculature and blood-contacting medical devices, have been poorly investigated. Very little previous work has been reported on the effects of extensional stresses on platelet activation; yet, when a platelet flows through a stenosis or enters a mechanical circulatory support (MCS) system, convective acceleration of blood flow produces such stresses ( Figure 1 ) [ [13] , [14] , [15] ]. Typical cases of extensional stresses are found in areas of sudden contractions or expansions of the flow field, such as the entrance and exits of ventricular assist devices, reverse gap flow in artificial heart valves, microcirculation, and entrance to severe arterial stenoses [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neither study observed any hemolysis, nor did they attempt to examine any possible markers of sublethal damage. The enhanced deformation under elongational stresses would suggest that this type of flow might be more damaging both in terms of hemolysis and sublethal damage [47].…”
Section: Effect Of Elongational Stressmentioning
confidence: 99%
“…In contrast to the measurement of cell rheology in the shear flow field of the ektacytometer, recent work indicates that cells deform to a greater extent in an elongational flow field than they do in a shear field of the same stress level [45]. Researchers in this area have typically used microfluidics with a converging bilaterally symmetric hyperbolic channel or a crossflow channel reminiscent of Taylor's 4-roll mill [47]. In these systems, DI is found from images of cells moving along the centerline.…”
Section: Indication Of Sublethal Trauma From Measurement Of Erythrocy...mentioning
confidence: 99%